Penerapan Model Problem Based Learning Pada Pembelajaran IPAS Kelas IV di SD - Yuliana Pujiningsih; Isnaini Wahyuningrum; Alfian Ahmad Kurniawan; Alfianahmad821@gmail.com (Jurnal Pendidikan Sosial Dan Konseling, 2024)
PBL is a learning process that begins with a "problem" rather than a presentation/explanation of knowledge or know-how (D.Boud, G. Feletti, 1987 in Introduction to PBL, Djauhari Widjajakusumah). In PBL, the problem is presented first before knowledge is provided. The problem presented must ask about a problem in a comprehensive manner, application, analysis and synthesis. Students must choose the knowledge they need, study it, and relate it to the problem given. The use of the PBL (Problem-Based Learning) method arises from the concept that students will find it easier to find and understand difficult concepts if they discuss it with their friends and always active in the learning process. Students routinely work in groups to help each other solve complex problems. Based on this statement, the author uses descriptive research with a qualitative approach. In this research the author tries to describe the events and occurrences that are the focus of this research and are described as they naturally exist.